New Zealand adolescents' concerns about their alcohol use and access to services: Associations with ethnicity and other factors. Issue 4 (2nd October 2019) - Ameratunga, Shanthi; Jackson, Nicki; Peiris-John, Roshini; Sheridan, Janie; Moselen, Emma; Clark, Terryann
ABSTRACT: Using a national survey of 8, 500 New Zealand high school students, we investigated adolescents' concerns about their drinking, associated factors including help-seeking preferences and access to health care services, and how these varied by ethnicity and level of socioeconomic deprivation. Approximately 23.9% of the 3, 704 current drinkers reported concerns (i.e., being worried about their drinking and/or having tried to cut down). Regression analyses revealed that Māori and Pacific youth were more likely than their New Zealand European peers to be concerned about their drinking. Concerned drinkers were more likely than nonconcerned drinkers to report hazardous drinking behaviors and alcohol-related problems, but these associations varied by age, ethnicity, and socioeconomic deprivation. Help-seeking preferences differed strongly by ethnicity. Concerned drinkers, and Māori and Pacific drinkers, were more likely to report difficulties accessing health care and alcohol and drug services. The factors associated with adolescents' drinking concerns and paradoxical difficulties accessing health care highlight the importance of engaging adolescents in developing responsive and equitable services.